2002
DOI: 10.1073/pnas.102674699
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of NF-κB DNA– protein interactions

Abstract: We describe a general method based on principal coordinates analysis to predict the effects of single-nucleotide polymorphisms within regulatory sequences on DNA-protein interactions. We use binding data for the transcription factor NF-B as a test system. The method incorporates the effects of interactions between base pair positions in the binding site, and we demonstrate that such interactions are present for NF-B. Prediction accuracy is higher than with profile models, confirmed by crossvalidation and by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 33 publications
6
95
1
2
Order By: Relevance
“…Early structural and biochemical experiments shed some light on the rules that discern the selection of kB target sites by the various NF-kB dimers. Ongoing systematic analysis of interactions combined with quantitative biochemical and biophysical studies may improve our predictive understanding of the specificity rules (Udalova et al, 2002). Although gene knockout studies have shown that biochemical affinity data are often not sufficient to explain the functional specificity in vivo of NF-kB dimers in gene expression, kB DNA-NF-kB interactions are probably a critical prerequisite for NF-kB in vivo function.…”
Section: Dna Recognition By Nf-jb Dimersmentioning
confidence: 99%
“…Early structural and biochemical experiments shed some light on the rules that discern the selection of kB target sites by the various NF-kB dimers. Ongoing systematic analysis of interactions combined with quantitative biochemical and biophysical studies may improve our predictive understanding of the specificity rules (Udalova et al, 2002). Although gene knockout studies have shown that biochemical affinity data are often not sufficient to explain the functional specificity in vivo of NF-kB dimers in gene expression, kB DNA-NF-kB interactions are probably a critical prerequisite for NF-kB in vivo function.…”
Section: Dna Recognition By Nf-jb Dimersmentioning
confidence: 99%
“…In the first data set (NF-κB [11]) only DNA target sequences vary. In the second (EGR [6]) both amino acids and nucleotides vary, but only in a limited number of positions.…”
Section: Introductionmentioning
confidence: 99%
“…We started by building regression models for NF-κB TF data (from [11]). This problem should be the easiest to solve, since only the DNA target sequences, and not the TFs varied (although two alternative TFs were examined).…”
Section: Applying Rule Induction To Nf-κb-dna Binding Datamentioning
confidence: 99%
See 2 more Smart Citations